2020
DOI: 10.1111/exd.14100
|View full text |Cite
|
Sign up to set email alerts
|

Association study between vitiligo and autoimmune‐related genes CYP27B1, REL, TNFAIP3, IL2 and IL21

Abstract: Experimental Dermatology. 2020;29:535-538. | 535 wileyonlinelibrary.com/journal/exd 1 | BACKG ROU N D Vitiligo is a pigmentary disease characterized by epidermal melanocyte loss resulting in white patches on the affected skin areas.Autoimmunity has been well accepted as a possible cause for vitiligo; in addition, evidence of a polygenic transmission of common, low-effect-size risk alleles was found within multiplex-vitiligo-affected families, as well as high heritability (h 2 ~ 0.75), [1] suggesting an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Vitiligo is considered to be an autoimmune disease because cytokines such as (IFN)-γ, IL-1, IL-6, IL-8, and IL-10 are overexpressed in lesions, and activated CD8 + T lymphocytes, TH17, and other immune cells are significantly aggregated in the lesion area (16)(17)(18)(19). However, some researchers have suggested that autoimmunity may be secondary to high oxidative stress in vitiligo skin, leading to inherent defects of melanocytes and changes in its microenvironment (4).…”
Section: Discussionmentioning
confidence: 99%
“…Vitiligo is considered to be an autoimmune disease because cytokines such as (IFN)-γ, IL-1, IL-6, IL-8, and IL-10 are overexpressed in lesions, and activated CD8 + T lymphocytes, TH17, and other immune cells are significantly aggregated in the lesion area (16)(17)(18)(19). However, some researchers have suggested that autoimmunity may be secondary to high oxidative stress in vitiligo skin, leading to inherent defects of melanocytes and changes in its microenvironment (4).…”
Section: Discussionmentioning
confidence: 99%
“…VEGFA, also known as vascular endothelial growth factor A, is considered to be a particularly interesting candidate gene, which has been attributed to its polymorphisms, its correlation with autoimmune disorders, and its induction of angiogenic factor expression in vitiligo; moreover, VEGFA may be a potential target for late-onset vitiligo therapy ( Almasi-Nasrabadi et al, 2019 ). IL2 has been implicated in the regulatory pathways of autoimmune diseases, including signaling and promotion of the growth and proliferation of T cells; therefore, this protein plays an important role in generating immune responses ( Martins et al, 2020 ). Finally, MPO-specific markers are strongly associated with microscopic polyangiitis and other autoimmune diseases ( Prendecki et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…40 Links between other gene candidates and vitiligo are under investigation. [42][43][44][45][46][47][48][49][50] 3.4 | Comorbidities, psychosocial effects and QoL…”
Section: Genetic Components and Biomarkersmentioning
confidence: 99%
“…In addition, elevated serum TNFα levels have been associated with vitiligo in Iraqi 41 and Iranian patients 40 . Links between other gene candidates and vitiligo are under investigation 42–50 …”
Section: Burden Of Vitiligo In Africa the Middle East And Latin Americamentioning
confidence: 99%
See 1 more Smart Citation